Afrikaner Odyssey: The Life and Times of the Reitz Family - Van der Waag, Ian (Scientia Militaria - South African Journal of Military Studies, 2019)
Deneys Reitz (1882–1944), the acclaimed memoirist and author of Commando, is arguably the best known of his gifted family.1 Several generations before him played interesting roles in the history of South Africa. The progenitor, Jan Frederik Reitz (1761–1824), was a Dutch naval officer, and then a Cape civil servant, before becoming a substantial landowner. His marriage into the influential Van Reenen family assisted as a social escalator. They had four sons and a daughter. Of these, Francis William (1810–1881) was a Swellendam agriculturalist and politician, and was returned in 1854 as one of the youngest members of the Cape Parliament of Francis William’s twelve children, a daughter married WP Schreiner, later a prime minister of the Cape Colony, and a son, another Francis William (1844–1934), served as president of the Orange Free State, then as state secretary of the South African Republic (Transvaal), and after 1910, as the first present of the Senate of the Union of South Africa. His talented sons included legal men, politicians, an author and poet, and another Union senator, as well as Deneys, the soldier-politician and trusted confidant of General Jan Smuts.